Mother Goose : nursery rhymes - Wildsmith, Brian (Oxford : Oxford University Press, 1964)
An illustrated collection of popular Mother Goose rhymes, including "Humpty Dumpty," "Old Mother Hubbard," and "Jack and Jill."
Keywords: Nursery rhymes